Facebook ad campaign management system enhancement - Sia, Cheng Yong (2018)
The advertising landscape have been changing over the decades as technology improves. Over the recent two decades, as digital technology improves, internet users grew by approximately 10 times. As Web 2.0 fully takes over the digital world, social media became the next platform that facilitates the creation and sharing of information. Likewise, businesses have evolved over the years from the traditional brick and mortar models to online retails. As a result, digital platforms are increasingly incorporated into marketing plans and every life. Digital marketing and online advertising has become a prominent source for many advertisers to reach out to a significantly huge customer base. Social media platforms such as Facebook, Instagram and YouTube etc. has become some of the most widely-used advertising marketing channels. Facebook itself, garner most of its revenue through advertising and reached three million active advertisers with more than 70% outside the US in March 2016. Optimate created a Facebook Ad Campaign Management System to help businesses optimize and automate their digital marketing with improved return of investments. Using insights from past campaigns, Optimate strives to streamline the process of serving the advertisements to the most suitable audiences to achieve greater key performance indicator results. In this project, the student is tasked to come up with innovations to improve the existing system and suggest possible strategies to enhance the current algorithm. The project consists of three main enhancements made to the existing system. The first two being new strategies being designed and implemented by the student to be added to the optimisation process and the last, the streamlining improvements made by the student. There may be more sub tasks depending on the progress and requirements of the project, as Optimate sees fit. Hence, this report will attempt to explain some of the strategies, methodologies and learning experience based on the aspects the student was involved.